Adaptation and Transformation of Honestdocs Business Model In The Era of Digital Health Technology - Saragi, Sahat; P., Embriana Dinar; Jamaludin, Aditya (Sciences of Pharmacy, 2026)
The rapid development of digital health technology has encouraged startups to continuously adapt their business models in response to regulatory, technological, and market challenges. This study aims to explore how a digital health startup in Indonesia adapts and transforms its business model within the evolving digital healthcare ecosystem. This research employed a qualitative exploratory case study design focusing on HonestDocs as a single case. Data were collected through semi-structured in-depth interviews with three key informants representing strategic managerial roles and were analyzed using thematic analysis following Braun and Clarke’s framework. To enhance credibility, interview findings were compared with selected internal documents and operational information. The findings indicate that business model adaptation in this case is characterized by three main patterns: the use of lightweight digital infrastructure, the integration of personalized customer service, and flexible operational strategies in responding to regulatory and logistical constraints. The study also shows that organizational culture and collaborative work practices appear to play an important role in supporting operational adaptability. However, the findings should be interpreted with caution, as this study is based on a single case and relies primarily on internal managerial perspectives, which may limit generalizability. Despite these limitations, the study provides exploratory insights into how digital health startups in emerging markets may respond to structural constraints and evolving user needs.